Perbedaan Motivasi Belajar Online Siswa IPA Dan IPS dalam Pembelajaran Ekonomi - Anjellita Dwi Febrin; Syamwil Syamwil (Jurnal Ecogen, 2022)
This study aims to determine the differences in students' online learning motivation for science and social studies in economics learning at SMA N 1 Akabiluru Lima Puluh Kota Sumatra Barat. This type of research is quantitative with a comparative method. The population in this study amounted to 166 students and the number of samples using the Slovin formula was 138. The data used were primary data types obtained through distributing questionnaires to grade 12 students of SMA N.1 Kec.Akabiluru. The analytical method used is a different test. The results showed that the results of the Independent sample T-Test obtained results of 0.00 <0.05, which means that there is a significant difference in online learning motivation between XII IPA and XII IPS students at SMA N 1 Akabiluru. These differences are influenced by (1) diligently working on assignments, (2) tenacity in facing difficulties, (3) showing interest in various problems, (4) preferring to work independently, (5) getting bored quickly in doing. Task. routine tasks, (6) Can defend opinions, (7) not easy to let go of things that are believed, (8) Likes to find and solve problems. Keywords : learning motivation, online learning, economics